2010
DOI: 10.1007/s00404-009-1347-y
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant/antioxidant status in premenstrual syndrome

Abstract: Increased oxidative stress and reduced antioxidant capacity may occur in PMS. It can be speculated that the imbalance of oxidant/antioxidant systems may be a cause or the consequence of the various stress symptoms in PMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
1
10

Year Published

2010
2010
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 26 publications
1
50
1
10
Order By: Relevance
“…In a preliminary study, subjects with PMS showed no evidence of oxidative damage [48]. In two studies that used malondialdehyde (MDA) as a marker of oxidative stress, no difference was observed between PMS patients and controls [5,49]. Conversely, a study by Duvan et al [5] reported a significant difference in LPH levels between controls and patients with PMS, and they found that TAC was significantly decreased in the PMS group.…”
Section: Role Of Oxidative Stress and Pon-1 In Pmddmentioning
confidence: 97%
See 4 more Smart Citations
“…In a preliminary study, subjects with PMS showed no evidence of oxidative damage [48]. In two studies that used malondialdehyde (MDA) as a marker of oxidative stress, no difference was observed between PMS patients and controls [5,49]. Conversely, a study by Duvan et al [5] reported a significant difference in LPH levels between controls and patients with PMS, and they found that TAC was significantly decreased in the PMS group.…”
Section: Role Of Oxidative Stress and Pon-1 In Pmddmentioning
confidence: 97%
“…In two studies that used malondialdehyde (MDA) as a marker of oxidative stress, no difference was observed between PMS patients and controls [5,49]. Conversely, a study by Duvan et al [5] reported a significant difference in LPH levels between controls and patients with PMS, and they found that TAC was significantly decreased in the PMS group. Importantly, the authors did not evaluate well-known confounding factors such as depression, anxiety, and sleep quality.…”
Section: Role Of Oxidative Stress and Pon-1 In Pmddmentioning
confidence: 99%
See 3 more Smart Citations